2021
DOI: 10.52082/jssm.2021.413
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Daily Distribution of Carbohydrate, Protein and Fat in Youth Tennis Players over a 7-Day Training and Competition Period

Abstract: During a 7-day training and/or competition period, macronutrient intake and distribution was assessed using food diaries, supported by remote food photography and 24-hr multiple pass recalls of youth tennis players categorised by under 12s, under 14s and under 16+ age groups (n = 27). Total energy did not differ between age groups nor type of day (training [TD], competition day [CD]), irrespective of a significant increase in body mass reported in the older players (U16+; p < 0.05). Average intakes were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Whether open stance and closed stance will affect the hitting speed and joint force, Fillmore and Hall think that open stance will cause a greater load on the athlete's body; however, some studies have also found that closed stance forehands have greater peak shoulder internal rotation torque and greater peak wrist flexion torque; this is in contrast to the idea that open stance shots place a greater load on the upper body [ 8 ]. Fleming et al study the characteristics of trunk muscle activation during open and closed forehand strokes in tennis; the results of the study do not support the hypothesis that open poses produce greater trunk muscle activation than closed poses; the external oblique is important in axial rotation, and female tennis players may require greater external oblique activation due to fewer external oblique muscle fibers [ 9 ]. While Bankosz and Winiarski suggested that the upper extremity dynamics of the open and closed forehand are very similar, except for the peak torque in shoulder internal rotation and wrist flexion, all subjects developed shoulder internal rotation torque during the forward swing, and the closed shoulder internal rotation torque was significantly greater than the open one, and the wrist flexion torque was also significantly greater [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whether open stance and closed stance will affect the hitting speed and joint force, Fillmore and Hall think that open stance will cause a greater load on the athlete's body; however, some studies have also found that closed stance forehands have greater peak shoulder internal rotation torque and greater peak wrist flexion torque; this is in contrast to the idea that open stance shots place a greater load on the upper body [ 8 ]. Fleming et al study the characteristics of trunk muscle activation during open and closed forehand strokes in tennis; the results of the study do not support the hypothesis that open poses produce greater trunk muscle activation than closed poses; the external oblique is important in axial rotation, and female tennis players may require greater external oblique activation due to fewer external oblique muscle fibers [ 9 ]. While Bankosz and Winiarski suggested that the upper extremity dynamics of the open and closed forehand are very similar, except for the peak torque in shoulder internal rotation and wrist flexion, all subjects developed shoulder internal rotation torque during the forward swing, and the closed shoulder internal rotation torque was significantly greater than the open one, and the wrist flexion torque was also significantly greater [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yli-Piipari 23 established five female NCAA Division 1 players to consume 2011 ± 207 kcal . day −1 , and Fleming et al 25 reported intakes consistently below 2250 kcal . day −1 irrespective of age group (ranging from 12–20 year olds).…”
Section: Resultsmentioning
confidence: 97%
“…40 Research to date largely fails to consider the distribution and timing of dietary intake, limited to two studies. 23,25 Initial insights suggest a lack of nutritional planning, with no clear differences in nutritional intake (total caloric intake and macronutrient distribution) established between type of day (rest, training, competition) nor meal (breakfast, lunch, dinner, snacks). This raises concerns regarding nutritional knowledge and the amount of time players spend planning and considering their dietary intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations